2021
DOI: 10.5194/amt-14-1379-2021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of co-located refractory black carbon (rBC) and elemental carbon (EC) mass concentration measurements during field campaigns at several European sites

Abstract: Abstract. The mass concentration of black carbon (BC) particles in the atmosphere has traditionally been quantified with two methods: as elemental carbon (EC) concentrations measured by thermal–optical analysis and as equivalent black carbon (eBC) concentrations when BC mass is derived from particle light absorption coefficient measurements. Over the last decade, ambient measurements of refractory black carbon (rBC) mass concentrations based on laser-induced incandescence (LII) have become more common, mostly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 110 publications
0
24
1
Order By: Relevance
“…Due to the large contribution of anthropogenic BC emissions on our measurements and the high uncertainty in the size distribution for diameters below the SP2 detection limit, we do not fit the size distribution to a log-normal distribution. Furthermore for M BC , diameters below 100 nm do not play a significant role, regardless of their potentially dominating role for N BC and importance for the BC surface area (Seinfeld and Pandis, 2006;Pileci et al, 2021;Schwarz et al, 2008;Reddington et al, 2013).…”
Section: Airborne Bc Measurementsmentioning
confidence: 94%
“…Due to the large contribution of anthropogenic BC emissions on our measurements and the high uncertainty in the size distribution for diameters below the SP2 detection limit, we do not fit the size distribution to a log-normal distribution. Furthermore for M BC , diameters below 100 nm do not play a significant role, regardless of their potentially dominating role for N BC and importance for the BC surface area (Seinfeld and Pandis, 2006;Pileci et al, 2021;Schwarz et al, 2008;Reddington et al, 2013).…”
Section: Airborne Bc Measurementsmentioning
confidence: 94%
“…There are various BC measurement methods exploiting different properties of BC and thus measuring different quantities (Petzold et al, 2013): elemental carbon (EC) determined by thermal and/or thermal-optical methods, equivalent BC (eBC) by optical absorption methods, and refractory BC (rBC) by incandescence methods. The different types of BC measurements (EC, eBC, and rBC) usually agree with each other within a factor of 2 (AMAP, 2022;Pileci et al, 2021). However, it has been shown that, as the aerosol ages, the complex state of mixing of BC particles causes eBC to increase relative to EC (Zanatta et al, 2018).…”
Section: Bc and Oamentioning
confidence: 97%
“…The Japanese measurements provide rBC (refractory BC). Pileci et al (2021) showed that rBC and eBC are linearly related; thus, in order to compare the observations to models, we converted rBC to eBC via a factor of 1.8 (eBC = 1.8 × rBC; Zanatta et al, 2018;Pileci et al, 2021).…”
Section: Ship Campaignsmentioning
confidence: 99%
“…Measurements of M EC can depend on the temperature protocol and optical charring correction method used (e.g., Bond et al, 2013). Agreements within 10 % of M BC (SP2), M BC (COSMOS), and M EC were reported by Kondo et al (2011), whereas systematic differences between M BC (SP2) and M EC up to a factor of 2 were found by Pileci et al (2021). Although the difference between M BC (COSMOS) and M EC was generally lower than 5 ng m −3 at the Arctic site Barrow (Sinha et al, 2017), this difference can be important for pristine summer Arctic conditions (M BC (COSMOS) <20 ng m −3 ).…”
Section: Measurements Of M Bc By Cosmosmentioning
confidence: 99%